Young people and their imagined futures. To which society do they appeal? (Praxis Educativa, 2023)
Through their establishment, societies create their temporality asan emergence of alterity and d ifference,which implies their present and future project for society and individuals. However, with the expansion ofneoliberal capitalism that undertakes the evacuation of the past, our current time is considered unique andinfinite, jeopardizing the future project that society would offer the subjects. From this perspective andbased on what young Mexicans pro pose about the future, the article reflects on the project thatcontemporary society provides to young people, who, in their creative processes of identity, appeal to theimaginary meanings that the community has to offer them to conformas subjects and articulate theirdesires in future-to-future projects.
Keywords: Youth; Future society; Imaginary meanings; Life projects; Formation